Free Medicines thanks to Retirement: Moral Hazard and Hospitalization Offsets in an NHS - Jaume Puig-Junoy; Pilar Garcia-Gomez; David Casado-Marin (Tinbergen Institute, 2011)
This paper examines the impact of coinsurance exemption for prescription medicines applied to elderly individuals in Spain after retirement. To evaluate this coinsurance change we use a rich administrative dataset that links pharmaceutical consumption and hospital discharge records for the full population aged 58 to 65 in January 2004 covered by the public insurer in a Spanish region and we follow them until December 2006. We use a difference-in-differences strategy and exploit the eligibility age for Social Security to control for the endogeneity of the retirement decision. Our most conservative results show that the uniform exemption from pharmaceutical copayment granted to retired people in Spain increases the consumption of prescription medicines on average by 9.5%, total pharmaceutical expenditure by 15.2% and the costs borne by the insurer by 47.5%, without evidence of any offset effect in the form of reduced hospitalization. The impact is concentrated among individuals who were consumers of medicines for acute and other non-chronic diseases with a previous coinsurance rate in the range 30% to 40%.
urn:NBN:nl:ui:15-1765/25710
Keywords: G22; I18; J14; 330; pharmaceuticals; cost sharing; hospitalization offsets; health care expenditure; Pharmazeutisches Produkt; Gesetzliche Krankenversicherung; Moral Hazard; Alte Menschen; Gesundheitskosten; Spanien